2012
DOI: 10.4314/thrb.v14i1.9
|View full text |Cite
|
Sign up to set email alerts
|

The potential of involving traditional practitioners in the scaling up of male circumcision in the context of HIV prevention in Tanzania

Abstract: Male circumcision (MC) has been practiced worldwide for religious, cultural, social and medical reasons. Recent studies in Africa have indicated that MC to be highly protective against HIV transmission. However, incorporating MC in HIV/AIDS prevention programme will increase its demand in Tanzania where traditional male circumcision is common and the health care system is weak. The objective of this study was to determine the challenges and opportunities of involving traditional practitioners in scaling up saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…This is in keeping with the observation that MC is widely accepted in Tanzania as reported in various studies (Nnko et al, 2001;Weiss et al, 2008;Wambura et al, 2009;Mshana et al, 2011, Kilima et al, 2012. Previous studies in sub Saharan Africa have reported on strategies to scale up MC ( Ngalande et al, 2006;WHO, 2007;Wambura et al, 2009) such as circumcision campaigns in non-circumcising communities, reducing the cost for a circumcision procedure and sensitizing women attending RCH clinics.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is in keeping with the observation that MC is widely accepted in Tanzania as reported in various studies (Nnko et al, 2001;Weiss et al, 2008;Wambura et al, 2009;Mshana et al, 2011, Kilima et al, 2012. Previous studies in sub Saharan Africa have reported on strategies to scale up MC ( Ngalande et al, 2006;WHO, 2007;Wambura et al, 2009) such as circumcision campaigns in non-circumcising communities, reducing the cost for a circumcision procedure and sensitizing women attending RCH clinics.…”
Section: Discussionsupporting
confidence: 78%
“…In the situational analysis report to the Ministry of Health and Social Welfare it was recommended that the services be provided free of charge to boys aged less than 10 years (Wambura et al, 2009). In another study in three districts of Tanzania, Kilima et al (2012) proposed that male circumcision procedure should be covered under the current health insurance schemes.…”
Section: Discussionmentioning
confidence: 99%
“…However and it is believed that, the technique varies from one ethnic group to another (Kilima et al, 2012). This is reflected by the extent of removal of foreskin and on the part removed whether ventral or dorsal.…”
Section: The Practice In Tanzaniamentioning
confidence: 99%
“…For example it has been witnessed that Gogo tribe in central Tanzania circumcise in such a way that a flap of foreskin is folded back under the ventral aspect of the penis to make a small swelling considered to have sexual functions (Kilima et al, 2012). Maasai on the other hand leave a hanging flap of foreskin on ventral aspect of the shaft of the penis, which is also considered to increase female stimulation during coitus and in other ethnic groups the foreskin is completely removed (Kilima et al, 2012). As indicated earlier, in traditional male circumcision neither anaesthesia nor analgesics are used with aim of testing bravery, endurance and strength of the participants.…”
Section: The Practice In Tanzaniamentioning
confidence: 99%
See 1 more Smart Citation